Evaluation of the Function of Referral System in Family Physician Program in Northern Provinces of Iran: 2008 - SD Nasrollahpour Shirvani,; H Ashrafian Amiri; ME Motlagh,; MJ Kabir; MR Maleki,; A Shabestani Monfared,; R Alizadeh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2010)
BACKGROUND AND OBJECTIVE: Health care system is organized at three levels in order to increase efficacy and effectiveness and create justice and also people availability. Considering three levels of primary health care, access of people to specialized services through referral system is possible. With regard to the importance of referral system in family physician program, this study was performed to evaluate the function of referral system and network system of medical universities in Northern provinces of Iran. METHODS: This analytic study was performed in Autumn of 2008. Twenty percent of health centers (108 centers from 521) which implement the family physician program and rural insurance coverage by medical Universities of Golestan, Mazandaran, Babol and Guilan were randomly selected. In each center 5-7 patients who were referred to level 2 by their family physician and received necessary services were evaluated. They were at their homes at inquiry time.FINDINGS: From 675 patients who received the level 2 services, 440 cases (65%) were female and 235 (35%) were male. Two hundred and seventy cases (40.5%) had referral form from health house. Only 311 (46%) persons referred because of diagnosis of family physician and in 212 (32.9%) of cases, the family physician had a role to choose a specialist of level 2. For 189 (28.1%) of cases, the specialists wrote the results of their evaluation in feedback form. Only 163 (24.5%) of patients returned to their family physicians. Three hundred ninety-four (79.6%) of patients didn return to their family physician because of lack of knowledge.CONCLUSION: The results of this study showed that many principles for referral system from level 1 to higher levels and vice versa are not considered that require education, reformation and intervention in this field.